Food export restrictions during the Covid-19 crisis - Laborde Debucquet, David (International Food Policy Research Institute, 2020)
Food Export Restrictions Tracker developed by David Laborde (IFPRI). Support for this work was provided by the CGIAR Research Program on Policies, Institutions, and Markets.